Optimalisasi Peran Perpustakaan Optimalisasi Peran Perpustakaan dalam Meningkatkan Motivasi Literasi Menulis Pemustaka Melalui Program Professor Goes to Library : Studi di Perpustakaan UIN Sunan Kalijaga Yogyakarta - Abdul Aziz, Sendysyah; Marwiyah (Institut Agama Islam Negeri (IAIN) Curup, 2025)
Abstract This study examines the effectiveness of the Professor Goes to Library program as a strategic initiative to enhance users’ motivation and academic writing literacy at the UIN Sunan Kalijaga Library. The program responds to persistent issues of low student motivation to write, limited academic guidance, restricted access to expert mentors, and inadequate facilities supporting scientific writing. Employing a qualitative case study design, data were gathered through in-depth interviews, observations, and documentation involving students, librarians, and professors engaged in the program. The findings indicate that the initiative substantially increases students’ motivation and confidence in producing scientific work, improves their understanding of academic structure, and strengthens their skills in citation and idea development. Direct interaction with professors fosters a more personal, open, and solution-oriented learning atmosphere, effectively addressing gaps in academic mentoring previously faced by users. The program also provides added value for librarians and professors by reinforcing their educational roles and enhancing the library’s position as an active learning and literacy hub. Although challenges remain—such as limited promotion, facility constraints, and the lack of continuous evaluation—the program demonstrates strong potential as an innovative model for improving academic writing literacy in higher education libraries.